Implementation of an At-home Blood Pressure Measurement Protocol in a Hypertension Management Clinical Trial During the COVID-19 Pandemic. Issue 5 (23rd September 2022) - Miller, Hailey N.; Berger, Miriam B.; Askew, Sandy; Trefney, Elizabeth; Tyson, Crystal; Svetkey, Laura; Bennett, Gary G.; Steinberg, Dori M.
Abstract : Background: The Dietary Approaches to Stop Hypertension eating plan is an evidence-based treatment of hypertension; however, adherence to the Dietary Approaches to Stop Hypertension is low. To improve adherence to the Dietary Approaches to Stop Hypertension among adults with hypertension, we designed Nourish, a 2-arm, 12-month randomized controlled trial. The COVID-19 pandemic necessitated a change from in-person to remotely delivered visits, requiring substantial protocol modifications to measure blood pressure accurately and safely for secondary outcome data. Purpose: The purpose of this article is to describe the implementation of an at-home blood pressure measurement protocol for the Nourish trial. Conclusion: Our investigator team and study staff developed and implemented a robust and feasible blood pressure measurement protocol to be executed within an at-home format. Clinical Implications: The described blood pressure measurement protocol provides a framework for use in future clinical trials and clinical settings in which a remote visit is preferred or required.